Psychosocial distress among patients with cancer at a county referral hospital in Kenya - Justin Kinoti, Francis; Oluchina, Sherry; Wambua Mbithi, Bernard (International Journal of Advanced Nursing Studies, 2020)
Introduction: Cancer diagnosis and treatment are emotionally draining to patients and their caregivers. For a long time, treatment for cancer has been associated with pain, suffering and death. These negative consequences of cancer create psychosocial effects such as anxiety and fear. Therefore, there is need to recognize and accurately identify this psychosocial distress problems on patients with cancer by healthcare providers to figure out interventions for these psychosocial issues.Objective: To assess the psychosocial distress among patients with cancer attending the Machakos county referral hospital palliative care unit.Subjects and Methods: Data were collected through descriptive cross-sectional design where a total of 97 patients were interviewed and filled the questionnaires and the National Cancer Center Network distress thermometer and problem list. The data was analyzed using the Statistical Package for Social Sciences (SPSS) for windows version 24. Descriptive statistics such as the means, standard deviation and frequencies were generated and Pearson Chi square test of association computed to determine the associations between the independent and the dependent variables. The confidence interval was set at 95% (p≤ 0.05).Results: The study findings revealed that 72.2% of the respondents were distressed. Majority (83.3%) of the respondents reported being in pain, 64.9% of them cited problems with decision making about treatment, while 59.8% of the respondents said that they were experiencing fatigue. Other issues cited by the respondents included financial constraints and facing difficulties while eating. The study results also showed that there was statistically significant association between having psychosocial distress and gender (P=0.015) and cancer treatment (P=0.015).Conclusion: There is a very high prevalence of psychosocial distress among patients with cancer with the leading psychosocial distress problem being pain.